JERAGAN NEMEN: DINAMIKA HUBUNGAN BAKUL-LANGGAN DALAM PERSPEKTIF POLITIK EKONOMI - M. Alie Humaedi (Masyarakat Indonesia, 2010)
So far, the vendor-customer (bakul-langgan) relationship is blamed for perpetuating poverty in the fisherman community. This patron-client relationship has disadvantaged fisherman as customers (langgan), and hasbrought advantages to vendors (bakul) as jeragan nemen because of their possession of production tools. This position has hardly changed, and the cultural aspect has received a more dominant position than the structural factors in causing poverty. This development is unfortunate, because when the state and the global market could not reach them, this traditional institution(bakul-langgan) would sustain the lives of poor fisherman. The wave of reform in 1998 has also transformed this custom institution. It began to lose its patron client relationship. Today, the vendor customer relationship has become more functional, and every aspect is negotiable. In addition, there is also a matter of desecration of debt which is given by bakul. Finally, the spirit of reform has also changed the position of jeragan nemen to langgan,and many of the subordinates (pendega) have become small business leaders. However, the involvement of rent seeking actors such as banks and micro finance institutions on behalf of cooperatives could bring back the fishermen to poverty.